Hubungan antara Penggunaan Smartphone pada Malam Hari dan Insomnia pada Remaja di Kota Mataram - Amanullah, Mohammad Sany Rosafi; Hunaifi, Ilsa; Diatmika, I Putu (Majalah Kedokteran Indonesia, 2025)
Introduction: Smartphone use among adolescents, particularly in Mataram City, West Nusa Tenggara, is highly prevalent. Nighttime smartphone useis associated with delayed sleep onset, as it extends the time adolescents more time to engage in various activities. Several studies have shown that smartphones use can contribute to sleep disturbances, including insomnia. This study aims to investigate the relationship between nighttime smartphone use and insomnia among adolescents in Mataram City.Methods: This study employed a cross-sectional design and included 362 students from Mataram City, selected through non-probability consecutive sampling method. Participants completed questionnaires assessing nighttime smartphone use and insomnia symptoms using Insomnia Severity Index. Data were analyzed using Spearman’s rank correlation test.Result: Of the total sample (44.5% male), the majority were 16 years old (62.4%), enrolled in Grade 11 (82.6%), and most (66.9%) were in the natural science program. The majority of participants were classified as having subclinical insomnia (43.9%), while only 2.5% experienced severe insomnia. The findings revealed a positive correlation between the frequency of nighttime smartphone and insomnia among adolescents (r=0.104; p=0.049).Conclusion: There is a significant relationship between the frequency of nighttime smartphone use and insomnia among adolescents in Mataram City.